Lower availability of midbrain serotonin transporter between healthy subjects with and without a family history of major depressive disorder – a preliminary two-ligand SPECT study - Hsieh, P.C.; Chen, K.C.; Yeh, T.L.; Lee, I.H.; Chen, P.S.; Yao, W.J.; Chiu, N.-T.; Chen, C.-C.; Liao, M.-H.; Yang, Y.K. (European psychiatry, 2014)
Serotonin transporter (SERT) and dopamine transporter (DAT) levels differ in patients with major depressive disorder (MDD) who are in a depressed state in comparison with healthy controls. In addition, a family history of depression is a potent risk factor for developing depression, and inherited vulnerability to serotonergic and dopaminergic dysfunction is suspected in this. The aim of this study was to examine the availabilities of midbrain SERT and striatal DAT in healthy subjects with and without a first-degree family history of MDD. Eight healthy subjects with first-degree relatives with MDD and 16 sex- and age-matched healthy controls were recruited. The availabilities of SERT and DAT were approximated using SPECT, employing [123I] 2-((2-((dimethylamino)methyl)phenyl)thio)-5-iodophenylamine (ADAM) and [99mTc] TRODAT-1 as the ligands, respectively. There are missing data for one participant with a first-degree family history of MDD from the ADAM study, due to a lack of the radio-ligand at the time of experiment. SERT availability in the midbrain was significantly lower in subjects with a first-degree family history of MDD than in healthy subjects. However, DAT availability was no different between two groups. The results with regard to the midbrain SERT level suggest the heritability of MDD.